Allison A. James, 1918. - Farrell's Studio (Forsyth County Public Library, 1918)
Source: Booklet, "Winston-Salem, City of Industry," 1918.
Allison A. James, 1918. Mr. James was president and treasurer of Yerkes Chemical Company, and president of Thompson Drug Company.
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works